Farnesoid X Receptor, Bile Acid Metabolism, and Gut Microbiota - Hideki Mori; Gianluca Svegliati Baroni; Marco Marzioni; Francesca Di Nicola; Pierangelo Santori; Luca Maroni; Ludovico Abenavoli; Emidio Scarpellini (Metabolites, 2022)
Obesity, type 2 diabetes, and non-alcoholic fatty liver disease (NAFLD) are characterized by the concepts of lipo- and glucotoxicity. NAFLD is characterized by the accumulation of different lipidic species within the hepatocytes. Bile acids (BA), derived from cholesterol, and conjugated and stored in the gallbladder, help the absorption/processing of lipids, and modulate host inflammatory responses and gut microbiota (GM) composition. The latter is the new “actor” that links the GI tract and liver in NAFLD pathogenesis. In fact, the discovery and mechanistic characterization of hepatic and intestinal farnesoid X receptor (FXR) shed new light on the gut–liver axis. We conducted a search on the main medical databases for original articles, reviews, meta-analyses of randomized clinical trials, and case series using the following keywords, their acronyms, and their associations: farnesoid X receptor, bile acids metabolism, gut microbiota, dysbiosis, and liver steatosis. Findings on the synthesis, metabolism, and conjugation processes of BAs, and their action on FXR, change the understanding of NAFLD physiopathology. In detail, BAs act as ligands to several FXRs with GM modulation. On the other hand, the BAs pool is modulated by GM, thus, regulating FXRs functioning in the frame of liver fat deposition and fibrosis development. In conclusion, BAs passed from their role of simple lipid absorption and metabolism agents to messengers between the gut and liver, modulated by GM.